2021
DOI: 10.1080/20008198.2021.1930960
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy was noninferior to verbal standard treatment of traumatized refugees in mental health care: Results from a randomized clinical trial

Abstract: Background: Many people with refugee backgrounds suffer from trauma-related complex social and psychological problems, and compliance with standard psychological treatment tends to be low. More culturally adaptable treatment options seem to be needed. Objective: We aimed to investigate whether the music therapy method: 'trauma-focused music and imagery' (tr-MI), characterized by a particular focus on arousal and affect regulation, would be equally effective as the standard psychological talk therapies for amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 60 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…After sixteen GIM sessions, adult refugees showed positive improvements in PTSD symptoms, sleep quality, well-being, and social functioning [ 98 ]. A recent randomized control trial with 74 refugees with PTSD, employing western classical music, New Age music, and music from the participants’ own national culture showed improvements in quality of life and fewer symptoms of psychological dissociation after music therapy [ 99 ]. In addition, unlike the standard treatment, the positive effects of music and imagery were manifested even at the 6 month follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After sixteen GIM sessions, adult refugees showed positive improvements in PTSD symptoms, sleep quality, well-being, and social functioning [ 98 ]. A recent randomized control trial with 74 refugees with PTSD, employing western classical music, New Age music, and music from the participants’ own national culture showed improvements in quality of life and fewer symptoms of psychological dissociation after music therapy [ 99 ]. In addition, unlike the standard treatment, the positive effects of music and imagery were manifested even at the 6 month follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review on music interventions for mechanically ventilated patients reported participant dropout rates to be higher in researcher-selected music compared to patient-selected [ 125 ]. Instead, studies involving a music therapist to assess patient music preferences have reported no dropouts and a high degree of participant satisfaction [ 70 , 98 , 99 ]. Therefore, self-selected music appears to be associated with both the effectiveness of music interventions and participant retention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different modalities of music therapies exert different effects on PTSD phenotypes aside from the cardinal symptoms. Guided imagery and music (GIM) significantly decreases the symptoms of dissociation (Maack, 2012 ; Story and Beck, 2017 ); GIM in the trauma-focused group of patients enhanced PTSD patients' quality of life and wellbeing (Rudstam et al, 2017 ; Beck et al, 2021 ); songwriting treatment reduced the numbing and depressive symptoms of PTSD patients (Coulter, 2000 ; Precin, 2011 ; Hirschberg et al, 2020 ), and playing musical instruments, such as drums or guitars, increased the sense of openness and togetherness, and facilitated non-intimidating access to traumatic memories in PTSD patients (Bensimon et al, 2008 ; Pezzin et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, music therapy has been shown to exhibit significant effects on trauma symptoms (e.g., it improves wellbeing and sleep quality) in traumatized refugees (Jespersen and Vuust, 2012 ; Beck et al, 2018a , 2021 ). There is abundant theoretical and empirical evidence concerning the beneficial effects of music therapy on PTSD patients ( Table 3 ).…”
Section: Introductionmentioning
confidence: 99%